Taxonomic novelties and new records of Fennoscandian crustose lichens - Svensson, Måns; Ekman, Stefan; Klepsland, Jon T.; Nordin, Anders; Thor, Göran; von Hirschheydt, Gesa; Jonsson, Fredrik; Knutsson, Tommy; Lif, Mattias; Spribille, Toby; Westberg, Martin (MycoKeys, 2017)
We present taxonomic, distributional and ecological notes on Fennoscandian crustose lichens and lichenicolous fungi, based on new collections as well as revision of herbarium material. Two new combinations are proposed: Frutidella furfuracea comb. nov. for F. pullata and Puttea duplex comb. nov. for Fellhanera duplex. Lecidea byssoboliza, L. carneoglauca and Variolaria torta are all reduced to synonymy with Bacidia antricola, Bacidia invertens is synonymized with B. igniarii, B. atrolivida with Mycobilimbia tetramera, and Gyalidea fruticola with Thelenella pertusariella. A new description is provided for Micarea hylocomii. 25 species of lichens and lichenicolous fungi are reported as new to Finland, Norway and/or Sweden: Absconditella lignicola (Norway), Bacidia antricola (Norway), B. polychroa (Norway), B. pycnidiata (Sweden), Bacidina adastra (Sweden), Biatora veteranorum (Norway), Briancoppinsia cytospora (Finland), Catillaria scotinodes (Norway), Cliostomum subtenerum (Norway), Dirina fallax (Sweden), Fellhaneropsis almquistiorum (Norway), Gyalidea subscutellaris (Sweden), Lecania inundata (Norway), L. suavis (Norway), Micarea capitata (Norway), M. deminuta (Norway), M. hylocomii (Sweden), M. lynceola (Sweden), M. soralifera (Sweden), M. subconfusa (Sweden), Mycoblastus sanguinarioides (Finland, Sweden), Paralecia pratorum (Sweden), Puttea duplex (Sweden), Sarcogyne algoviae (Finland) and Toninia subnitida (Norway). Lectotypes are designated for Bacidia antricola, Lecidea byssoboliza, Lecidea carneoglauca, Lecidea subconfusa and Lecidea submoestula.